Pengembangan Electronic Personal Health Record Anak Sekolah Dasar Di Kota Tasikmalaya - Imas Masturoh; Andi Suhenda; Fery Fadly (Politeknik Negeri Jember, 2024)
The COVID-19 pandemic has caused various impacts in many places, including schools. COVID-19 has led to the closure of many schools to control the spread of the virus, resulting in disruptions to medical services such as regular check-ups for students. The development of E-PHR is effort to monitor the health status of students. This study aimed to design an E-PHR sistem for elementary school students in Tasikmalaya. This research used an RnD type with the SDLC method. The research subjects were selected using purposive sampling, consisting of UKS (School Health Unit) activity managers at the Tasikmalaya City Health Office, all Community Health Centers in Tasikmalaya City, and teachers responsible for UKS. This study used data accumulation techniques through in-depth interviews and focus groups. A needs analysis was conducted to facilitate data collection and retrieval as well as reporting to the health office level. The research results showed that the recording of health issues for students in schools obtained from preventive check-ups, health examinations, and screening results by the UKS team at schools is still not optimal because it is done manually and directly. Therefore, it is recommended that elementary schools, health centers, and the health office prepare the necessary equipment to implement this sistem.